积极心理学视角下大学生心理健康教育模式构建研究 - 赵文青 (现代高等教育研究, 2026)
Positive psychology, with its core tenets of identifying human strengths, cultivating virtues, and pursuing happiness, provides a novel theoretical perspective for mental health education for college students. This paper analyzes the value implications of college students’ mental health education from the perspective of positive psychology, and explores the foundational applications of positive psychology theory in this field. Furthermore, it proposes strategies for constructing a mental health education model for college students based on positive psychology, aiming to better promote students’ mental health and personality development.